2022
DOI: 10.15549/jeecar.v9i2.829
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brand equity on investor loyalty in online securities trading using the Technology Acceptance Model

Abstract: The more equity a brand has, the stronger its behavioral loyalty, according to branding theory. This research adopted the technology acceptance model framework to explain the impact of brand equity on investors' loyalty in online securities trading. Our data was collected via a multi-method approach, and using a structured survey, the impact of brand equity on behavioral loyalty was tested. The findings indicate that brand equity impacts behavioral loyalty but does not influence mediators. This research also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this sense, the main themes explored in the publications on this subject were grouped through clustering, which associates the keywords and main themes of publications in a visual representation [83]. Cluster 1, represented by the color red, addresses aspects of brand management that stimulate CBBE and one of its main dimensions, brand loyalty [84][85][86][87][88][89]. The stimulation of CBBE involves the consumer experience [58,90], experiences in tourist destinations, and the quality of services offered in the hotel sector [37,56,91].…”
Section: Characterization Of the Theoretical Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the main themes explored in the publications on this subject were grouped through clustering, which associates the keywords and main themes of publications in a visual representation [83]. Cluster 1, represented by the color red, addresses aspects of brand management that stimulate CBBE and one of its main dimensions, brand loyalty [84][85][86][87][88][89]. The stimulation of CBBE involves the consumer experience [58,90], experiences in tourist destinations, and the quality of services offered in the hotel sector [37,56,91].…”
Section: Characterization Of the Theoretical Fieldmentioning
confidence: 99%
“…The stimulation of CBBE involves the consumer experience [58,90], experiences in tourist destinations, and the quality of services offered in the hotel sector [37,56,91]. Branding and marketing Cluster 1, represented by the color red, addresses aspects of brand management that stimulate CBBE and one of its main dimensions, brand loyalty [84][85][86][87][88][89]. The stimulation of CBBE involves the consumer experience [58,90], experiences in tourist destinations, and the quality of services offered in the hotel sector [37,56,91].…”
Section: Characterization Of the Theoretical Fieldmentioning
confidence: 99%
“…Thus, it can be indicated that brand meaning also covers the complexity of brand management process. This concept then leads to the creation of Behavioral Loyalty from the customers (Borirakcharoenkit et al, 2022) so that the meaning encoded from the brand (logo) represents its social categories at the same time. David Allen Aaker (Kusumah et al, 2020) recognized the combination between brand and its contained meaning as Brand Management, saying that brand is not merely a symbol but also implies its benefit through brand attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Resource-based theory (Barney, 1991), which places intangible assets as determinants of small business success which several sub-factors considered as variables shaping business success: personal branding (Alonso- Gonzalez et al, 2019;Potgieter & Doubell, 2020), corporate branding (Borirakcharoenkit et al, 2022;Pranjal & Sarkar, 2020;Vinuales & Sheinin, 2020), Open Innovation (Akinwale, 2018;Valdez-Juárez & Castillo-Vergara, 2021), financial literacy (Mutamimah et al, 2021;Resmi, 2019).…”
Section: Introductionmentioning
confidence: 99%